2022
DOI: 10.3390/vaccines11010084
|View full text |Cite
|
Sign up to set email alerts
|

Durability of ChAdOx1 nCoV-19 (Covishield®) Vaccine Induced Antibody Response in Health Care Workers

Abstract: (i) Background: ChAdOx1 nCoV-19 (Covishield®) vaccine is widely used in India. We studied the Covishield® induced antibody response and its durability among health care workers (HCWs) (ii) Method: HCWs received two doses (0.5 mL) four weeks apart. Blood specimens, collected before each dose, day (D)60, D150 and D270 after second dose, were tested for anti-spike antibody (ASAb) titre and neutralising antibody (%) (NAb) using Elecsys Anti-SARS-CoV-2 S (Roche) and SARS-CoV-2 NAb ELISA Kit (Invitrogen), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Asymptomatic coronavirus infection is widespread in the low-risk general population as well. Similarly, high seroprevalence of ASAb has been observed in other group of unvaccinated populations such as health care workers, 16 people with cirrhosis, 17 or renal transplant recipients. 18 An Indian study from a quarantine facility in the state of Karnataka showed that 90% of the infection remains asymptomatic in the community.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Asymptomatic coronavirus infection is widespread in the low-risk general population as well. Similarly, high seroprevalence of ASAb has been observed in other group of unvaccinated populations such as health care workers, 16 people with cirrhosis, 17 or renal transplant recipients. 18 An Indian study from a quarantine facility in the state of Karnataka showed that 90% of the infection remains asymptomatic in the community.…”
Section: Resultsmentioning
confidence: 72%
“…Asymptomatic coronavirus infection is widespread in the low‐risk general population as well. Similarly, high seroprevalence of ASAb has been observed in other group of unvaccinated populations such as health care workers, 16 people with cirrhosis, 17 or renal transplant recipients 18 …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations